Membangun Konsep Diri Mantan Narapidana Dalam Masyarakat - Edison Bonar Tua Hutapea (Oratio Directa (Prodi Ilmu Komunikasi), 2023)
AbstractThe public's perception of ex prisoner is sometimes a bit excessive, so that it can affect the ex's perception of themselves. Experience of ex prisoner experiencing social discrimination, making it difficult for them to find decent jobs. It is this good adaptation process in society that will later change the negative stigma of society towards former persons with disabilities. Good adaptation process in society will later change the negative stigma of society towards former ex prisoner. Ex prisoner seeing his self or his self-concept can be negative. Self concept is not only a descriptive description, but also other human assessment, self-concept is something that is thought and felt by an individual Key words: Self concept, ex prisoner, society